The Relationship between Hospital Market Competition, Evidence-Based Performance Measures, and Mortality for Chronic Heart Failure - Jared Lane K. Maeda; Anthony T. Lo Sasso (SAGE Publishing, 2012)
Using data from the Joint Commission's ORYX initiative and the Medicare Provider Analysis and Review file from 2003 to 2006, this study employed a fixed-effects approach to examine the relationship between hospital market competition, evidence-based performance measures, and short-term mortality at seven days, 30 days, 90 days, and one year for patients with chronic heart failure. We found that, on average, higher adherence with most of the Joint Commission's heart failure performance measures was not associated with lower mortality; the level of market competition also was not associated with any differences in mortality. However, higher adherence with the discharge instructions and left ventricular function assessment indicators at the 80 th and 90 th percentiles of the mortality distribution was associated with incrementally lower mortality rates. These findings suggest that targeting evidence-based processes of care might have a stronger impact in improving patient outcomes.